معايير الأخلاق بين السنة النبوية ومفاهيم الغرب : دراسة تحليلية مقارنة - عامري، غصنه حمد متعب (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to define the moral standard and its forms in Islam and in the West. It elucidates the impact of Islamic and Western moral standards in society and compares them accordingly. The importance of this research reflects in presenting analytical study that observes the standards of Western morality and their comparison with the standards of Muslims morality prescribed in the Qur'an and hadith. The study has employed inductive, analytical and comparative methods to collect and track the ethical ideas stated in hadith and in Islamic references, to scrutinise hadith assembled in their books and in their commentaries in order to find out opinions of scholars concerning to the standards of morality and to compare between the morals of Muslims and the morals of the West based on articulated variables that contain points of similarity and difference respectively. The most important findings of the study are that the ethics is a normative science that should be thought accordingly. Human beings should furnish themselves according to the norms of morality without paying attention to what are the ethics of people. The multiplicity of moral orientations in Western philosophy and the different approaches of philosophers, led to the construction of ethics based on ration and the anomalies of some moral doctrines in Western philosophy resulted in linking morality to all that ascertain material happiness of man from pleasures and desires. Christianity has transformed its certain Old Testament values through the New Testament as it made love the basis of its most of the moral standards. And lastly the Abrahamic faiths did not only pay attention to oneness of God and His worship, but they combined both doctrinal and moral aspects simultaneously in their injunctions.